2022
DOI: 10.1002/ppp.2143
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ecological succession and climate warming on permafrost aggradation in drained lake basins of the Tuktoyaktuk Coastlands, Northwest Territories, Canada

Abstract: Rapidly increasing air temperatures will alter permafrost conditions across the Arctic, but variation in soils, vegetation, snow conditions, and their effects on ground thermal regime complicate prediction across spatial and temporal scales. Processes that result in the emergence of new surfaces (lake drainage, channel migration, isostatic uplift, etc.) provide an opportunity to assess the factors influencing permafrost aggradation and terrain evolution under a warming climate. In this study we describe ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 134 publications
0
1
0
Order By: Relevance
“…The formation and drainage of lakes have shaped lake and drained lake basin (L‐DLB) landscapes in lowland permafrost regions (Grosse et al., 2013; Jones et al., 2022). The long‐term evolution of L‐DLB landscapes is well documented (Jorgenson & Shur, 2007; Wolfe et al., 2020); however, few studies have directly observed L‐DLB surface dynamics in the field using observational data sets (e.g., Arp et al., 2023; Jones & Arp, 2015; Jones et al., 2023b; Lantz et al., 2022). Even fewer studies have observed sub‐surface dynamics associated with sub‐lake permafrost thaw and talik formation (e.g., Creighton et al., 2018; Roy‐Leveillee & Burn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The formation and drainage of lakes have shaped lake and drained lake basin (L‐DLB) landscapes in lowland permafrost regions (Grosse et al., 2013; Jones et al., 2022). The long‐term evolution of L‐DLB landscapes is well documented (Jorgenson & Shur, 2007; Wolfe et al., 2020); however, few studies have directly observed L‐DLB surface dynamics in the field using observational data sets (e.g., Arp et al., 2023; Jones & Arp, 2015; Jones et al., 2023b; Lantz et al., 2022). Even fewer studies have observed sub‐surface dynamics associated with sub‐lake permafrost thaw and talik formation (e.g., Creighton et al., 2018; Roy‐Leveillee & Burn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DLBs have previously found to be sites of wetland formation (Lantz et al, 2022), however they have been mostly described as wetlands in older basins on centennial or millennial timescales. Following drainage, landcover of the area has a tendency to become more heterogeneous over time (Figure 5).…”
mentioning
confidence: 99%